EFEKTIVITAS PIJAT PERINEUM PADA IBU HAMIL TERHADAP LASERASI PERINEUM - Ratna Wulan Purnami; Endah Tri Wahyuni (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2019)
Women are entrusted with the task of becoming a mother who will later give birth to superior quality babies as the next generation to strengthen the nation's pillar towards a moral and dignified life and build a noble civilization. One indicator of improving maternal health is the reduction in maternal mortality associated with improving the quality of childbirth assistance. The Maternal Mortality Rate in Indonesia in 2015 reached 161 / 100,000 live births, still quite high from the target of 102 / 100,000 live births. Maternal mortality in Indonesia is still dominated by three main causes of death, namely bleeding, hypertension in pregnancy and infection. One of the main causes of bleeding is a tear in the birth canal, including the perineal laceration. Birth road tears are experienced by 85% of women giving birth. One preventive effort that can be done to prevent tears in the perineum during labor is perineal massage. Perineal massage aims to increase blood flow and increase the elasticity of the perineum. Increased perineal elasticity will prevent the occurrence of perineal tears and episiotomy. This study is an analytical study with a quasi-experimental design and prospective direction of investigation. The study population was all third trimester pregnant women in the working area of ​​the Kalasan Sleman Health Center. The sampling technique used a purposive sampling method that is sampling according to the considerations and criteria set by the researcher, the sample amounted to 40 pregnant (20 controls and 20 treatments). The results of the Mann Whitney SPSS 23 statistical analysis showed a 2-tailed significance value of 0.433> 0.05 which means Ha was rejected, thus there were no significant differences between the two groups. Whereas the mean treatment rank is 19.30 and the mean rank control is 21.70, which means there are differences in the average between the two groups.